2020
DOI: 10.1101/2020.04.15.043299
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human SLC46A2 is the dominant cGAMP importer in extracellular cGAMP-sensing macrophages and monocytes

Abstract: Administration of exogenous CDNs to activate the cGAMP-STING pathway is a promising therapeutic strategy to unleash the full potential of cancer immunotherapy. This strategy mirrors the role of endogenous extracellular cGAMP, which we recently described as an immunotransmitter exported by cancer cells and imported into local responder cells of unknown identities to promote anti-tumoral immunity, with irradiation enhancing this effect. Here, in low-dose irradiated murine tumors, we identified CD4 + T cells, M1 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 85 publications
(135 reference statements)
0
5
0
Order By: Relevance
“…Other second messengers such as cAMP and cGMP are only reported to have intracellular functions and intracellular regulation. In contrast, cGAMP has only been found to have extracellular regulation with a large number of known cGAMP transporters 9,11,21,[39][40][41][42] and hydrolases that are all extracellular. It thus seems reasonable that the grand majority of cGAMP regulation would occur in the extracellular space.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other second messengers such as cAMP and cGMP are only reported to have intracellular functions and intracellular regulation. In contrast, cGAMP has only been found to have extracellular regulation with a large number of known cGAMP transporters 9,11,21,[39][40][41][42] and hydrolases that are all extracellular. It thus seems reasonable that the grand majority of cGAMP regulation would occur in the extracellular space.…”
Section: Discussionmentioning
confidence: 99%
“…It thus seems reasonable that the grand majority of cGAMP regulation would occur in the extracellular space. Indeed, we have shown that the presence of cytosolic DNA leads to the production of extracellular cGAMP to mediate immunity in a STING-dependent manner 8,11,13 . Together, we propose a model in which cGAMP’s main physiological function is that of a paracrine immunotransmitter 8,13,43,44 , and the differential expression of Enpp1 and Enpp3 regulate how much cGAMP cells emit and receive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The only mammalian protein that degrades cGAMP is ENPP1, a cell membrane‐bound esterase with extracellular activity (Li et al , 2014). Recent evidence suggests that cGAMP is transported across membranes by channel proteins and can thus be exported from and/or imported into cells (Luteijn et al , 2019; Ritchie et al , 2019; Carozza et al , 2020; preprint: Cordova et al , 2020; preprint: Lahey et al , 2020; Zhou et al , 2020a; Zhou et al , 2020b). Specifically, cGAMP exported by cancer cells may have important roles in anti‐tumour immunity (Marcus et al , 2018; Carozza et al , 2020).…”
Section: Introductionmentioning
confidence: 99%